2022
DOI: 10.3389/fchem.2022.1046010
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed thickness engineering of tellurene for field-effect transistors and polarized infrared photodetectors

Abstract: Research on elemental 2D materials has been experiencing a renaissance in the past few years. Of particular interest is tellurium (Te), which possesses many exceptional properties for nanoelectronics, photonics, and beyond. Nevertheless, the lack of a scalable approach for the thickness engineering and the local properties modulation remains a major obstacle to unleashing its full device potential. Herein, a solution-processed oxidative etching strategy for post-growth thickness engineering is proposed by leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Two-dimensional (2D) semiconducting materials have been studied extensively as photodetectors because of their intriguing optical properties. Among them, transition metal dichalcogenides (TMDCs) are one of the most investigated owing to their widely tunable electronic bandgap ranging from ∼few tens meV to ∼2 eV. Even though various studies have reported the wafer-scale synthesis of TMDCs for CMOS-based applications, TMDCs are vulnerable to oxidation from ambient conditions, which have impeded their use as a replacement for Si technology. In the past few years, air-stable layered materials, such as n-type bismuth oxychalcogenides (Bi 2 O 2 Se), and monoelemental materials, such as p-type tellurene, have been synthesized by chemical vapor deposition (CVD) and hydrothermal synthesis and utilized for short wavelength infrared (SWIR) photodetectors and MIR at room temperature. Since photodetectors integrated with single 2D materials in the conventional transistor configuration exhibit very low photoresponses owing to their very small absorption cross section and only the interface of the gate (G)–source (S) and gate (G)–drain (D) contributing to the photocurrent induced by electron and hole separation at the Schottky barrier, vertically stacked photoreactors have been investigated to overcome this issue by maximizing photoactive area, i.e., highly enhanced absorption cross section. Among them, a vertically stacked van der Waals heterojunction, i.e., forming a p–n junction using two different kinds of materials, or the same type of polarity with different Fermi level has been reported for a high on/off ratio, superior interface quality because of the lack of dangling bonds in the 2D materials, and bandgap engineering due to numerous selections of van der Waals materials of various bandgaps and work function for p- and n-type semiconductors. , These devices usually exhibit a photoresponse toward fast photodetectors with rise or fall times of tens of μs to ms. , Even though a very slow photoresponse with a long retention time in vertically stacked heterostructured devices using van der Waals 2D materials has been recently reported, …”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) semiconducting materials have been studied extensively as photodetectors because of their intriguing optical properties. Among them, transition metal dichalcogenides (TMDCs) are one of the most investigated owing to their widely tunable electronic bandgap ranging from ∼few tens meV to ∼2 eV. Even though various studies have reported the wafer-scale synthesis of TMDCs for CMOS-based applications, TMDCs are vulnerable to oxidation from ambient conditions, which have impeded their use as a replacement for Si technology. In the past few years, air-stable layered materials, such as n-type bismuth oxychalcogenides (Bi 2 O 2 Se), and monoelemental materials, such as p-type tellurene, have been synthesized by chemical vapor deposition (CVD) and hydrothermal synthesis and utilized for short wavelength infrared (SWIR) photodetectors and MIR at room temperature. Since photodetectors integrated with single 2D materials in the conventional transistor configuration exhibit very low photoresponses owing to their very small absorption cross section and only the interface of the gate (G)–source (S) and gate (G)–drain (D) contributing to the photocurrent induced by electron and hole separation at the Schottky barrier, vertically stacked photoreactors have been investigated to overcome this issue by maximizing photoactive area, i.e., highly enhanced absorption cross section. Among them, a vertically stacked van der Waals heterojunction, i.e., forming a p–n junction using two different kinds of materials, or the same type of polarity with different Fermi level has been reported for a high on/off ratio, superior interface quality because of the lack of dangling bonds in the 2D materials, and bandgap engineering due to numerous selections of van der Waals materials of various bandgaps and work function for p- and n-type semiconductors. , These devices usually exhibit a photoresponse toward fast photodetectors with rise or fall times of tens of μs to ms. , Even though a very slow photoresponse with a long retention time in vertically stacked heterostructured devices using van der Waals 2D materials has been recently reported, …”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] But, the non-layered feature makes Te difficult to achieve a thin layer with a thickness less than 10 nm, which can limit the gatecontrol ability and device scaling potential. [21][22][23][24] In this work, we propose a facile thinning strategy for solution-proceed Te flakes, that enables an effective thinning of post-growth Te flakes from bulk (hundreds nm) to few-layer (below ten nm), remaining a high materials quality and guaranteeing the high efficient electrostatic doping as a transistor channel. Then, we fabricate a four-terminal architecture of JFETs by integrating the ultrathin Te with n-type ReS 2 flakes.…”
Section: Introductionmentioning
confidence: 99%